Analysis of Price Volatility in Natural Gas and Crude Oil Markets - Komarov, Vladimir (2023)
The present study aims to examine the return volatility of futures market prices for natural gas and crude oil during the time period of 2010-2023. It provides a comprehensive overview of the global natural gas and crude oil markets, as well as the European Union markets, highlighting the factors that contribute to the high volatility observed in these markets, such as supply and demand issues, political instability, and governance influences. To achieve the objectives, three different types of GARCH models, namely classic GARCH, GJR-GARCH, and EGARCH models, are employed for analysis and prediction. The primary aim of employ- ing these models is to identify the best fit for the selected commodities using the maximum likelihood function and MSE statistic. The analysis indicates that the crude oil market is best fitted with a EGARCH model, while the GARCH model is the best fit for the natural gas market. Furthermore, the paper offers a brief introduction to risk management, and based on the best fitting models for each time series, the Value at Risk (VaR) statistic is calculated and estimated.